Comparative efficacy and tolerability of probiotics for antibiotic-associated diarrhea: Systematic review with network meta-analysis. Issue 2 (March 2018) - Cai, Jiayi; Zhao, Chunyang; Du, Yajie; Zhang, Yaqiong; Zhao, Mingyi; Zhao, Qingchun
Background: Probiotics are commonly used for the prevention of antibiotic-associated diarrhea (AAD). However, the optimum regimen remains controversial. Objective: The objective of this article is to compare and rank the relative efficacy and tolerability among all available probiotic agents for AAD through a network meta-analysis. Methods: Eligible studies were identified by searching PubMed, Embase, Medline, Cochrane library and Web of Science for randomized controlled trials (RCTs) that examined the efficacy of probiotic therapy for AAD. A random-effects model was applied within a frequentist framework. Quality of evidence was performed by the GRADE approach. The project was prospectively registered with PROSPERO (CRD 42016050776). Results: Fifty-one articles (60 comparisons, 9569 participants), including 10 probiotic interventions, were identified. Lactobacillus rhamnosus GG (LGG) had the highest probability of being ranked best both in effectiveness (odds ratio (OR), 95% confidence interval (CI) = 0.28 (0.17, 0.47)) and tolerance (0.44 (0.23, 0.84)) on prevention of AAD. With regard to reducing Clostridium difficile infection rate, Lactobacillus casei ( L. casei ) was considered better efficacy (0.04 (0.00, 0.77)) and medium tolerance (0.56 (0.19, 1.66)). Strain combination reported no superiority over single strain in either efficacy or tolerability. Conclusions: LGG is probably the best option to consider when AAD is indicated. L. casei appears to be the most efficacious choice when associated with severe C. difficile- related cases.